Eve’s fig-leaf: The Male Narrator, Sophistry and the Loss of Narrative Innocence in The Mill on the Floss - Maria Tang (Cahiers Victoriens et Edouardiens)
The adoption of a male pseudonym by women writers in the nineteenth century is, as Elaine Showalter has pointed out, a sign of the woman writer’s loss of innocence, of her awareness of the necessity of role playing in order to enter the literary mainstream. In this paper, I intend to examine some of the self-conscious ambiguities of the role-playing narrator of The Mill on the Floss. The use of the male narrator is inseparably bound up with a number of compromises for the woman writer and for the female reader. But being thus ‘compromised’ through vicariously living the experience of the masculine Other also allows the woman writer privileged insight into the complex processes of justification and rationalisation through which the masculine worldview is engendered and sustained in narrative; it allows her imaginatively to work through, and to see through, the tangle of cause and effect relations which are often illegitimately marshalled into support of that view, and to cast ironical and critical light on them.